Financial Inclusion in Monetary and Banking Law - Belazzem, Mabrouk (Journal of Legal Studies and Researches, 2024)
Financial inclusion is among the goals that the new monetary and banking law seeks to achieve, and the dedication of this goal is demonstrated through the law’s adoption of a digital transformation strategy in the banking and financial field, and the recognition of new actor in the banking and non-banking sectors in addition to adopting and introducing new banking operations and activities that were not known.